Status sócio-econômico, background familiar e as chances de sucessos dos candidatos ao vestibular da UFC - Guimarães, Daniel Barboza (2008)
Analyzing the performance of candidates to the vestibular examination at the UFC is the man focus of this dissertation. This study, of aspect strictly empirical, is based upon econometric models discreet choice, binary and polychotomus, with the aim of extracting candidates' chances to achieve success in the vestibular. Such models were applied to the data base contained in the socioeconomic questionnaire filled out by the candidates themselves. It was verified that the results here obtained were shown compatible with other studies in the literature. Among the five socioeconomic variables taken for estimation, a fort negative effect was verified in the chance of succeeding in the college entrance exam for those candidates that are in the job market, just as theoretically expected. The rotten quality of the public schooling emerged in the results by reducing the chances of success for candidates from of public schools. Family background was incisive on candidates' successes, since those that possess parents with college education demonstrate to possess a better performance in the exam. By analyzing candidates' performance by area of knowledge, it could be concluded, within a scenario of optimistic forecast, that candidates with high chance of success in certain area would not maintain it in other areas. Such discrepancy was observed by comparing medicine and technology with other areas.